(untitled) - Cassese, Antonio (New York, 2008)
International Criminal Law provides a clear account of the principles governing international crimes and an outline of international criminal trials. Adopting a combination of the classic common law and more theoretical approaches to the subject, it expounds the fundamentals of both substantive and procedural international criminal law, providing a theoretical framework to all the rules, principles, concepts, and legal constructs key to the subject
Keywords: International offenses,Criminal procedure (International law),Tội phạm quốc tế,Thủ tục hình sự (luật pháp quốc tế)